ICT usage intensity in the Hungarian corporate sector: Stylised facts on microdata - Tamás Berki (Magyar Nemzeti Bank, 2023)
In this paper, we investigate the information and communication technology (ICT) usage patterns of Hungarian companies, relying on a company-level questionnaire survey conducted in 2020, and combining it with data from corporate annual reports. Our main objective is to construct an index of ICT usage patterns in the Hungarian business sector that reflects the digitisation level (ICT usage intensity) of companies and amalgamates into a single indicator the questionnaire survey information relevant to ICT usage. After aggregating (scoring) the qualitative questionnaire data, we used factor analysis to identify four distinct areas that are associated with the digitisation levels of the different business functions. These are the following: area responsible for integrating business functions, e-administration, IT infrastructure, and marketing and communications. The digitisation headline index is derived from the subindices of these four areas. Our paper also aims to map the patterns of ICT use by company size, sector, productivity and export activity. The intensity of ICT use is closely correlated with company size, export activity and productivity. Companies with more employees or higher productivity tend to be more intensive users of technologies. Firms that also export tend to use ICT more extensively than non-exporting ones. Technology use varies markedly from sector to sector, both in terms of the range of technologies used and their sophistication.
Keywords: C43; C81; L25; O30; 330; use of information and communication technologies; enterprise microdata; questionnaire survey; composite index; factor analysis